Challenges for EPTT teachers in the development of remote education in pandemic times (Research, Society and Development, 2022)
This research sought to analyze the challenges faced by EPTT teachers in developing classes in the mode of remote teaching in the face of a scenario of a global pandemic caused by Covid-19. The research was characterized as quantitative-qualitative, exploratory and descriptive, started with a bibliographic review and subsequent application of questionnaires to EPT teachers of the disciplines of the basic axis belonging to the Federal Institute of Education, Science and Technology of Maranhão, Campus São Luís Monte Castelo, through online data collection tools. The results show that one of the main challenges for EPTT teachers is related to the expansion of the training process in TIDs and their educational methodologies. The challenges in offering remote education to EPTT teachers are diverse and must be overcome in the new reality of post-pandemic education, in order to contribute to the reflection on training, actions and improvement in the quality of teaching and learning.